2022
DOI: 10.7150/ijbs.71390
|View full text |Cite
|
Sign up to set email alerts
|

Mechanosensitive Piezo1 is crucial for periosteal stem cell-mediated fracture healing

Abstract: The biomechanical environment plays a dominant role in fracture healing, and Piezo1 is regarded as a major mechanosensor in bone homeostasis. However, the role of Piezo1 in fracture healing is not yet well characterized. In this study, we first delineated that Piezo1 is highly expressed in periosteal stem cells (PSCs) and their derived osteoblastic lineage cells and chondrocytes. Furthermore, downregulation of Piezo1 in callus leads to impaired fracture healing, while activation by its specific agonist promote… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
29
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 38 publications
(29 citation statements)
references
References 76 publications
0
29
0
Order By: Relevance
“…Osteogenesis and vascularization are intimately coupled during bone regeneration, and the reconstruction of blood flow provides nutritional support for bone injury repair. , It has been reported that both angiogenesis and osteogenesis are regulated by cellular mechanical stress . The angiogenic ability of the MSNPs with magnetic signals was investigated via tube formation assay with human umbilical vein endothelial cells (HUVECs).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Osteogenesis and vascularization are intimately coupled during bone regeneration, and the reconstruction of blood flow provides nutritional support for bone injury repair. , It has been reported that both angiogenesis and osteogenesis are regulated by cellular mechanical stress . The angiogenic ability of the MSNPs with magnetic signals was investigated via tube formation assay with human umbilical vein endothelial cells (HUVECs).…”
Section: Resultsmentioning
confidence: 99%
“…39,40 It has been reported that both angiogenesis and osteogenesis are regulated by cellular mechanical stress. 41 The angiogenic ability of the MSNPs with magnetic signals was investigated via tube formation assay with human umbilical vein endothelial cells (HUVECs). As shown in Figure 4A, magneto-mechanical effects increase blood vessel formation.…”
Section: ■ Introductionmentioning
confidence: 99%
“…They found that Yoda1 could improve delayed fracture healing caused by mechanical unloading and increase the bone mass. [ 17,38 ] However, there were significant differences in the injection dose of Yoda1, ranging from 5 µmol kg −1 to 5 mmol kg −1 . A toxic concentration of Yoda1 can be quickly achieved by injecting Yoda1 alone.…”
Section: Discussionmentioning
confidence: 99%
“…Piezo1 is a mechanosensitive ion channel, which is widely expressed in epithelial cells, stem cells, , and cardiomyocytes . It senses extracellular mechanical stimuli and translates them into intracellular biochemical signals, which is involved in various physiological functions of cells. , Previous studies have reported that Piezo1 plays a critical role in maintaining bone homeostasis and that mice specifically knocked out of Piezo1 in osteoblasts usually have hypogenetic development. , Furthermore, hindlimb suspension mice and cellular rotation system osteoblasts suggested that mechanical unloading can inhibit Piezo1 expression, resulting in dysfunctional osteoblasts and bone formation. , Also, Piezo1 was required to adapt to external mechanical fluid shear stress in MC3T3-E1 cells, which induced RUNX2 gene expression .…”
Section: Discussionmentioning
confidence: 99%